2011
DOI: 10.1182/blood-2011-05-355248
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of plasma prekallikrein or coagulation factor XII inhibits thrombosis in mice without increased risk of bleeding

Abstract: Recent studies indicate that the plasma contact system plays an important role in thrombosis, despite being dispensable for hemostasis. For example, mice deficient in coagulation factor XII (fXII) are protected from arterial thrombosis and cerebral ischemia-reperfusion injury. We demonstrate that selective reduction of prekallikrein (PKK), another member of the contact system, using antisense oligonucleotide (ASO) technology results in an antithrombotic phenotype in mice. The effects of PKK deficiency were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
186
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 46 publications
14
186
2
3
Order By: Relevance
“…40 Comparable results have been obtained using PKknockout mice, which indicates that PK inhibition could be a potential target for anticoagulation. 41 However, there are some contradictory results: inhibition of plasma kallikrein with different inhibitors produced a prothrombotic state, 42 which is a relevant observation for the further development of kallikrein inhibitors.…”
Section: Pksupporting
confidence: 53%
See 1 more Smart Citation
“…40 Comparable results have been obtained using PKknockout mice, which indicates that PK inhibition could be a potential target for anticoagulation. 41 However, there are some contradictory results: inhibition of plasma kallikrein with different inhibitors produced a prothrombotic state, 42 which is a relevant observation for the further development of kallikrein inhibitors.…”
Section: Pksupporting
confidence: 53%
“…Similar to what was seen for factor XI, antisense oligonucleotides to factor XII reduced thrombus formation in several mouse thrombosis models in both venous and arterial beds. 40 To our knowledge, no human trials have been performed with factor XII-inhibiting agents.…”
Section: Factor XIImentioning
confidence: 99%
“…15,16 In various animal models, decreasing or eliminating FXI procoagulant activity through gene knockout, pharmacologic inhibition, or antisense oligonucleotidemediated knockdown is also antithrombotic without significantly impairing hemostasis, [17][18][19][20][21] suggesting that FXI is an important driver of pathologic coagulation with only a supportive function in normal hemostasis. Interestingly, FXII and prekallikrein have also been shown to contribute to the development of experimental thrombosis in mice, 22,23 despite the normal to possibly prothrombotic phenotype associated with deficiency of either of these proteins (Hagemen trait and Fletcher trait, respectively) in humans. 14,[24][25][26] We previously demonstrated that FXI deficiency was associated with improved survival and reduced coagulopathy relative to wild-type mice during polymicrobial peritoneal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] These studies provide strong evidence for a role for FXII in pathological thrombosis in mice, although clinical evidence for an analogous role in humans is still lacking.…”
Section: Introductionmentioning
confidence: 96%